2001
DOI: 10.1097/00006676-200105000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Tumor Necrosis Factor-α, Interleukin-6, and Interferon-γ in Spontaneous Chronic Pancreatitis in the WBN/Kob Rat

Abstract: To clarify the pathophysiological significance of cytokines in chronic pancreatitis (CP), we analyzed tissue expressions of various cytokines in the onset and progression of spontaneous CP in the WBN/Kob rat. Four-week-old male WBN/Kob rats were fed a special pellet diet (MB-3) for 20 weeks, and 6 rats were killed every 4 weeks. Pathologically, CP occurred at 12 weeks and progressed thereafter. The inflammation and fibrosis peaked at 12 and 16 weeks, respectively. By semiquantitative reverse transcription-poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…The mRNA of both IFN-γ and IL-6 mRNA were elevated for liver specimens of a transgenic mouse model for chronic hepatitis C-virus liver disease. In spontaneous chronic pancreatitis in a rat model, IFN-γ was related to the progression of chronic pancreatitis (11). These findings are in agreement with the significantly increased IFN-γ serum levels detected in our series of PD patients.…”
Section: Oral Submucosis Fibrosis -(S) +(S) +(S)supporting
confidence: 92%
See 3 more Smart Citations
“…The mRNA of both IFN-γ and IL-6 mRNA were elevated for liver specimens of a transgenic mouse model for chronic hepatitis C-virus liver disease. In spontaneous chronic pancreatitis in a rat model, IFN-γ was related to the progression of chronic pancreatitis (11). These findings are in agreement with the significantly increased IFN-γ serum levels detected in our series of PD patients.…”
Section: Oral Submucosis Fibrosis -(S) +(S) +(S)supporting
confidence: 92%
“…They are well known to be involved in many fibrotic diseases (Table-3) of lung, liver, kidney, pancreas, and systemic aggressive fibromatosis as well as colloid and hypertrophic scar formation (8)(9)(10)(11)(12)(13). With the exception of a reported series from our group including a smaller patient population (14) to our knowledge there have been no further investigations of serum cytokine levels in PD.…”
Section: Commentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Szuster-Ciesielska et al observed increased TNF-alpha and IL-6 levels in alcoholic liver cirrhosis and chronic pancreatitis (18). To clarify the pathophysiological significance of cytokines in chronic pancreatitis, Xie et al analyzed tissue expressions of various cytokines in the onset and progression in rats with chronic pancreatitis and their results suggested that tissue expressions of TNF-alpha and IL-6 were involved in the onset of pancreatitis and that IFN-gamma expression was related to the progression of chronic pancreatitis (19).…”
Section: Discussionmentioning
confidence: 99%